Pengaruh Pola Hidup Terhadap Risiko Hipertensi Pada Dewasa Usia ≥18 Tahun - Cesaltina Bui Pereira; Gipta Galih Widodo (Akademi Keperawatan Yarsi Samarinda, 2026)
Hypertension is a non-communicable disease that poses a significant public health challenge both globally and nationally, with its prevalence continuously increasing among adults aged ≥18 years. This study aims to analyze the influence of lifestyle on the risk of hypertension in adults through a literature review, examining recent studies on diet, physical activity, smoking habits, caffeine consumption, and stress management. The review findings indicate that unhealthy lifestyle behaviors, such as excessive intake of salt, sugar, and fat, lack of physical activity, smoking, high caffeine consumption, and chronic stress, significantly increase the risk of hypertension. Conversely, adopting a healthy lifestyle can reduce blood pressure, prevent complications, and improve quality of life. These findings highlight the importance of community-based nursing interventions that include patient education, monitoring, and guidance to consistently implement lifestyle modifications